Strategy to identify and quantify polysaccharide gums in gelled food concentrates. (1st January 2015) - Grün, Christian H.; Sanders, Peter; van der Burg, Monique; Schuurbiers, Eric; van Adrichem, Linda; van Velzen, Ewoud J.J.; de Roo, Niels; Brunt, Kommer; Westphal, Yvonne; Schols, Henk A.
Highlights: Xanthan gum and locust bean gum (LBG) were determined in gelled food concentrates. The gums were identified by a combination of PCR, NMR, and enzymatic fingerprinting. Xanthan gum was quantified by monosaccharide analysis. LBG was selectively quantified by enzymatic fingerprinting using endo -β-mannanase. Recoveries for xanthan gum and LBG were 87 ± 16% and 70 ± 6%, respectively. Abstract: A strategy for the unambiguous identification and selective quantification of xanthan gum and locust bean gum (LBG) in gelled food concentrates is presented. DNA detection by polymerase chain reaction (PCR) showed to be a fast, sensitive, and selective method that can be used as a first screening tool in intact gelled food concentrates. An efficient isolation procedure is described removing components that may interfere with subsequent analyses. NMR spectroscopy enabled the direct identification of xanthan gum and the discrimination between different galactomannans in the isolated polysaccharide fraction. An enzymatic fingerprinting method using endo -β-mannanase, in addition to being used to differentiate between galactomannans, was developed into a selective, quantitative method for LBG, whereas monosaccharide analysis was used to quantify xanthan gum. Recoveries for xanthan gum and LBG were 87% and 70%, respectively, with in-between day relative standard deviations below 20% for xanthan gum and below 10% for LBG.